A representação do sagrado na arquitetura e na iconografia da Igreja Nossa Senhora Consolata, em Boa Vista - RR - Castro, Francisco Mário Ribeiro (2015)
Our Lady Consolata Church is the holly place made by Saint Vincent s community in Boa Vista city, State of Roraima. This temple, built in 1983, by Consolata s missionaries helped by catholic folk who lives in the district where the church is situated, is the result of the many social cultural and religious processes for what this catholic community has passed by. This temple, considered the holly place, suffered actually a reform and reorganizational process of its space. Such process, besides modifying the ancient architecture of the temple, added new elements and symbols and redimensioned its space by giving to it a new architecture. This work has as objective to analyse this process of reform but mainly to reflect about the meaning of the symbols and icons which were added by the reform process. In this analyses we start from the principle which the temple is the most holly place into the Christian catholic experience and because this such place must have symbol elements for helping the communication between prayer believer and theirs worshipped the divine be. Therefore this reflection will be done by trying to understand the meaning of the geometrycal shapes of the temple and all icons in its interior side such as: Cristo Pantokrator, the cross, the mosaics of the altar and Virgin Consolata icon. To come true the analyses we used the qualitative search methodology by taking as investigative tools such elements: searches in archives and bibliographies, talking groups and interviews. All this search work made us to realize that the composition process of the social group of Saint Vincent Paul s district and of Our Lady Consolata Community were the result from several rights and wrongs that is also the result from exodus process which the people was submited (or submited themselves), printind this way, a particular character in that religious group. Understand itself, therefore, that to create a worship space, was the motivation for fighting for a life space too. And in these experiences the folk was descovering itself , it was raising roots and it was growing up as cultural social and religious group by conquering its territory, identity and suverving. Followed in this perspective, we can say that , in this case, the worship space become itself an essential factor, such as conquests expression as important tool in this historic process, result from their creativity and frequent re-meaning required by the life, maily, for a people which knew re-invent own culture and their symbols.